Polymer composition for non-aqueous secondary battery and non-aqueous secondary battery
The polymer composition for non-aqueous secondary batteries, featuring specific ethylene monomer-derived units, addresses the challenge of achieving both good rebound and cycle characteristics by maintaining high mechanical properties and adhesion after electrolyte immersion, thus enhancing battery performance.
Patent Information
- Application Number
- JP2022570008
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-12-15
- Filing Date
- 2021-12-14
- Publication Date
- 2025-04-09
- Estimated Expiration
- 2041-12-14
AI Technical Summary
Existing methods for manufacturing electrodes for lithium-ion secondary batteries, such as those described in Patent Documents 1 and 2, fail to achieve both good rebound and cycle characteristics simultaneously due to insufficient adhesion and mechanical properties after immersion in the electrolyte.
A polymer composition for non-aqueous secondary batteries is developed, comprising polymer particles with specific units derived from ethylene monomers, which have a glass transition temperature and electrolyte swelling degree within specific ranges. This composition ensures a breaking strength of 2 MPa or more and a breaking elongation of 100% or more, even after immersion in the electrolyte.
The polymer composition achieves excellent rebound and cycle characteristics for non-aqueous secondary batteries, maintaining high mechanical properties and adhesion even after exposure to the electrolyte, thereby enhancing the battery's performance and longevity.
Smart Images

Figure 0007659575000001 
Figure 0007659575000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a polymer composition for a non-aqueous secondary battery and a non-aqueous secondary battery. [Background technology]
[0002] Conventionally, a method for producing an electrode used in an electrochemical device such as a lithium ion secondary battery includes applying a liquid composition containing an electrode active material and a binder, a thickener, etc., to the surface of a current collector and drying the liquid composition to form an electrode layer on the current collector. Here, styrene-butadiene copolymer latex is known as a binder that can form an electrode layer that has high adhesion to the metal constituting the current collector and is also highly flexible. Note that the binder functions to improve the adhesion between the electrode layer containing the active material and the current collector or separator, but the above-mentioned copolymer latex may have insufficient adhesion to the current collector or separator. If the adhesion is insufficient, the charge and discharge cycle characteristics of the secondary battery tend to be impaired.
[0003] In view of the above, Patent Document 1 proposes adjusting the breaking elongation and breaking strength of a sheet made from a binder composition obtained by dispersing a specific polymer in an organic solvent or water to a specific range, while Patent Document 2 proposes adjusting the tensile strength of a copolymer binder moistened with an electrolyte solution to a specific range. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Patent No. 6090213 [Patent Document 2] International Publication No. 2018 / 182343 Summary of the Invention [Problem to be solved by the invention]
[0005] It is said that the binder composition described in Patent Document 1 can provide a homogeneous and stable slurry for electrodes, while the binder composition for secondary batteries described in Patent Document 2 can improve the life performance of batteries by exhibiting improved adhesive strength and maintaining high mechanical properties even after immersion in an electrolyte solution. On the other hand, the inventors have found through their research that the desired strength cannot be achieved after immersion in an electrolyte solution by simply adjusting the breaking elongation and breaking strength of the polymer before immersion in an electrolyte solution based on the description in Patent Document 1, resulting in impaired rebound characteristics and cycle characteristics. In this specification, the rebound characteristic means the property of suppressing an increase in the thickness of a secondary battery electrode before and after being subjected to a certain charge / discharge cycle, and in particular, the strength of the binder component contained in the electrode tends to contribute to the rebound characteristic. Moreover, it has been found that when the tensile strength of the polymer after immersion in an electrolyte solution is adjusted based on the description in Patent Document 2, the absolute value of the strength does not reach a desired level, and as a result, sufficient rebound characteristics and cycle characteristics cannot be exhibited. As described above, according to the techniques described in Patent Documents 1 and 2, it is difficult to achieve both high levels of rebound characteristics and cycle characteristics.
[0006] The present invention has been made in consideration of the problems associated with the above-mentioned conventional techniques, and has an object to provide a polymer composition for a nonaqueous secondary battery and a nonaqueous secondary battery that can exhibit good rebound characteristics and cycle characteristics. [Means for solving the problem]
[0007] The present inventors have found that the above object can be achieved by using polymer particles having a specific composition or physical properties, and have thus completed the present invention.
[0008] That is, the present invention includes the following aspects. [1] A polymer composition for a non-aqueous secondary battery, comprising polymer particles having a unit U1 derived from an ethylenic monomer M1 and a unit U2 derived from an ethylenic monomer M2, The ethylenic monomer M1 has a glass transition temperature as a homopolymer of −60° C. or lower, and has a degree of swelling in an electrolyte of 1.4 times or less; The ethylenic monomer M2 has a glass transition temperature as a homopolymer of 100° C. or higher, and has a degree of swelling in an electrolyte of 1.2 times or less; When all units derived from ethylenically unsaturated monomers constituting the polymer particles are taken as 100 mass%, the content of the unit U1 is more than 50 mass%, and the content of the unit U2 is 5% or more and less than 50 mass%, The polymer composition for non-aqueous secondary batteries, wherein the polymer particles have a degree of swelling in an electrolyte of 1.3 times or less. [2] The polymer composition for nonaqueous secondary batteries according to [1], wherein the polymer particles have a breaking strength S of 2 MPa or more and a breaking elongation E of 100% or more, which are measured when the polymer particles are swollen in an electrolyte solution. [3] The polymer composition for a nonaqueous secondary battery according to [2], wherein a breaking strength ratio R1 between a breaking strength S0 of the polymer particle and the breaking strength S, and a ratio R2 between a breaking elongation E0 of the polymer particle and the breaking elongation E, which are obtained based on the following formulas 1 and 2, are ±40% or less and ±10% or less, respectively. [Calculation of breaking strength ratio R1] Breaking strength ratio R1 = {(breaking strength S0 / breaking strength S)-1} x 100 (Equation 1) (In the above formula 1, the breaking strength S0 represents the breaking strength measured on the polymer particles before immersion in the electrolyte solution.) [Calculation of breaking elongation ratio R2] Breaking strength ratio R2 = {(breaking elongation E0 / breaking elongation E) - 1} x 100 (Equation 2) (In the above formula 2, the breaking elongation E0 represents the breaking elongation measured on the polymer particles before immersion in the electrolyte solution.) [4] The polymer composition for non-aqueous secondary batteries according to any one of [1] to [3], wherein the ethylenic monomer M1 contains 2-ethylhexyl acrylate. [5] The polymer composition for non-aqueous secondary batteries according to any one of [1] to [4], wherein the ethylenic monomer M2 contains an ethylenically unsaturated carboxylic acid or an alkali metal salt thereof. [6] The polymer composition for non-aqueous secondary batteries according to any one of [1] to [5], wherein the ethylenic monomer M2 contains (meth)acrylic acid or an alkali metal salt thereof. [7] The polymer composition for a nonaqueous secondary battery according to any one of [1] to [6], wherein the maximum glass transition temperature of the polymer particles measured by DSC is 20° C. or lower. [8] The polymer composition for a nonaqueous secondary battery according to any one of [1] to [7], wherein the average particle size of the polymer particles is 50 nm or more and 800 nm or less. [9] The polymer composition for a nonaqueous secondary battery according to any one of [1] to [8], further comprising 0.0001 part by mass or more and 1.0 part by mass or less of an isothiazolinone compound relative to 100 parts by mass of the polymer particles.
[10] A polymer composition for a non-aqueous secondary battery comprising polymer particles, The degree of swelling of the polymer particles in an electrolyte solution is 1.3 times or less, The polymer composition for non-aqueous secondary batteries, wherein the polymer particles have a breaking strength S of 2 MPa or more and a breaking elongation E of 100% or more, measured when the polymer particles are swollen in an electrolyte solution.
[11] The polymer composition for a nonaqueous secondary battery according to
[10] , wherein a breaking strength ratio R1 of a breaking strength S0 to a breaking strength S of the polymer particles and a ratio R2 of a breaking elongation E0 to a breaking elongation E of the polymer particles, which are obtained based on the following formulas 1 and 2, are ±40% or less and ±10% or less, respectively. [Calculation of breaking strength ratio R1] Breaking strength ratio R1 = {(breaking strength S0 / breaking strength S)-1} x 100 (Equation 1) (In the above formula 1, the breaking strength S0 represents the breaking strength measured on the polymer particles before immersion in the electrolyte solution.) [Calculation of breaking elongation ratio R2] Breaking strength ratio R2 = {(breaking elongation E0 / breaking elongation E) - 1} x 100 (Equation 2) (In the above formula 2, the breaking elongation E0 represents the breaking elongation measured on the polymer particles before immersion in the electrolyte solution.)
[12] A negative electrode for a non-aqueous secondary battery, comprising the polymer composition for a non-aqueous secondary battery according to any one of [1] to
[11] .
[13] Use of the polymer composition for a non-aqueous secondary battery according to any one of [1] to
[11] as a material for a negative electrode of a non-aqueous secondary battery.
[14] A non-aqueous secondary battery comprising the polymer composition for non-aqueous secondary batteries according to any one of [1] to
[11] . Effect of the Invention
[0009] According to the present invention, it is possible to provide a polymer composition for a nonaqueous secondary battery and a nonaqueous secondary battery which are capable of exhibiting good rebound characteristics and cycle characteristics. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] Hereinafter, an embodiment of the present invention (hereinafter, also referred to as "the present embodiment") will be described in detail. Note that the present invention is not limited to the following embodiment, and can be practiced with various modifications within the scope of the gist of the present invention. In this specification, "(meth)acrylic" means "acrylic" and its corresponding "methacrylic." In addition, in this specification, unless otherwise specified, the numerical values on both ends of "to" are included as the upper and lower limits.
[0011] [Polymer composition for non-aqueous secondary batteries] A polymer composition for a non-aqueous secondary battery according to one aspect of this embodiment (hereinafter also referred to as "first composition") is a polymer composition for a non-aqueous secondary battery comprising polymer particles (hereinafter also referred to as "first polymer particles") having a unit U1 derived from an ethylenic monomer M1 and a unit U2 derived from an ethylenic monomer M2, wherein the ethylenic monomer M1 has a glass transition temperature as a homopolymer of -60°C or lower and the degree of swelling in an electrolyte of the ethylenic monomer M1 is 1. The ethylenic monomer M2 has a glass transition temperature of 100° C. or higher as a homopolymer, and the ethylenic monomer M2 has a swelling degree in an electrolyte of 1.2 times or less, and when the total units derived from the ethylenic unsaturated monomers constituting the polymer particles are taken as 100 mass%, the content of the unit U1 is more than 50 mass%, and the content of the unit U2 is 5% or more and less than 50 mass%, and the swelling degree in an electrolyte of the polymer particles is 1.3 times or less. Because of this constitution, the first composition can exhibit good rebound characteristics and cycle characteristics.
[0012] Further, a polymer composition for non-aqueous secondary batteries according to another aspect of this embodiment (hereinafter also referred to as "second composition") is a polymer composition for non-aqueous secondary batteries containing polymer particles (hereinafter also referred to as "second polymer particles"), in which the electrolyte swelling degree of the polymer particles is 1.3 times or less, the breaking strength S of the polymer particles is 2 MPa or more, and the breaking elongation E of the polymer particles is 100% or more, measured when the polymer particles are swollen in the electrolyte. As configured in this way, the second composition can also exhibit good rebound characteristics and cycle characteristics.
[0013] As described above, both the first composition and the second composition can exhibit good rebound characteristics and cycle characteristics. Hereinafter, when the term "composition of the present embodiment" is used, the present embodiment will be described as including the "first composition" and the "second composition". Similarly, when the term "polymer particles in the present embodiment" is used, the present embodiment will be described as including the "first polymer particles" and the "second polymer particles".
[0014] (First polymer particles) The first polymer particles have a predetermined content of a unit U1 and a unit U2.
[0015] (Unit U1) The unit U1 is a structural unit derived from an ethylenic monomer M1, and the glass transition temperature of the ethylenic monomer M1 as a homopolymer is -60°C or less, and the electrolyte swelling degree of the ethylenic monomer M1 is 1.4 times or less. Since the glass transition temperature and electrolyte swelling degree satisfy the above ranges, the unit U1 contributes as a soft component in the first polymer particle. From the same viewpoint as above, the glass transition temperature of the ethylenic monomer M1 as a homopolymer is preferably -62°C or less, more preferably -65°C or less. Similarly, the electrolyte swelling degree of the ethylenic monomer M1 is preferably 1.35 times or less, more preferably 1.3 times or less. The glass transition temperature and the swelling degree in an electrolyte solution can be measured by the method described in the Examples below. The glass transition temperature and the swelling degree in an electrolyte solution can be adjusted to the above ranges, for example, by selecting a monomer having a low SP value as the ethylenic monomer M1.
[0016] The ethylenic monomer M1 is not particularly limited as long as it satisfies the above glass transition temperature and electrolyte swelling degree, and specific examples thereof include acrylic acid esters such as heptyl acrylate, octyl acrylate, 2-ethylhexyl acrylate, isodecyl acrylate, etc., and methacrylic acid esters such as octyl methacrylate, lauryl methacrylate, octadecyl methacrylate, tetradecyl methacrylate, etc. As the ethylenic monomer M1, one of the above examples may be used alone, or two or more of them may be used in combination. In this embodiment, from the viewpoints of productivity and cost, the ethylenic monomer M1 preferably contains 2-ethylhexyl acrylate.
[0017] (Unit U2) The unit U2 is a structural unit derived from an ethylenic monomer M2, and the ethylenic monomer M2 as a homopolymer has a glass transition temperature of 100° C. or higher and a degree of swelling in an electrolyte of 1.2 times or less. Since the glass transition temperature and the swelling degree in the electrolyte satisfy the above ranges, the unit U2 contributes as a hard component in the first polymer particle. From the same viewpoint as above, the glass transition temperature of the ethylenic monomer M2 as a homopolymer is preferably 150° C. or higher, more preferably 200° C. or higher. Similarly, the swelling degree in the electrolyte of the ethylenic monomer M2 is preferably 1.15 times or lower, more preferably 1.10 times or lower. The glass transition temperature and the swelling degree in an electrolyte solution can be measured by the method described in the Examples below. The glass transition temperature and the swelling degree in an electrolyte solution can be adjusted to the above ranges, for example, by selecting a monomer having a low SP value as the ethylenic monomer M2.
[0018] The ethylenic monomer M2 is not particularly limited as long as it satisfies the above-mentioned glass transition temperature and swelling degree in the electrolyte solution, and specific examples thereof include ethylenic unsaturated carboxylic acids such as (meth)acrylic acid or alkali metal salts thereof, amide group-containing monomers such as (meth)acrylamide, etc. As the ethylenic monomer M2, one of the above examples may be used alone, or two or more of them may be used in combination. In this embodiment, from the viewpoint of productivity, the ethylenic monomer M2 preferably contains an ethylenically unsaturated carboxylic acid or an alkali metal salt thereof, more preferably contains (meth)acrylic acid or an alkali metal salt thereof, and even more preferably contains methacrylic acid or an alkali metal salt thereof.
[0019] (Other units) The first polymer particle may have a unit U3 other than the unit U1 and the unit U2. Examples of the monomer M3 that gives such an arbitrary unit U3 include, but are not limited to, (meth)acrylic acid esters not corresponding to the ethylenic monomer M1, such as methyl (meth)acrylate, ethyl (meth)acrylate, and butyl (meth)acrylate, aromatic vinyl monomers such as styrene and vinyl naphthalene, nitrile group-containing monomers such as (meth)acrylonitrile, sulfonic acid group-containing monomers such as vinyl sulfonic acid, aromatic divinyl monomers such as divinylbenzene, alkylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, and 1,9-nonanediol di(meth)acrylate, trimethylolpropane di(meth)acrylate. Examples of the silane coupling agents include polyol poly(meth)acrylates such as trimethylolpropane tri(meth)acrylate, pentaerythritol di(meth)acrylate, pentaerythritol di(meth)acrylate, and pentaerythritol tetra(meth)acrylate; allyl compounds such as diallyl fumarate, diaryl itaconate, and triallyl isocyanurate; and silane coupling agents such as vinyltrimethoxysilane, vinyltriethoxysilane, p-styryltrimethoxysilane, 3-methacryloxypropylmethyldimethoxysilane, 3-methacryloxypropyltrimethoxysilane, 3-methacryloxypropylmethyldiethoxysilane, 3-methacryloxypropyltriethoxysilane, and 3-acryloxypropyltriethoxysilane. Among the above-listed exemplified agents, one may be used alone, or two or more may be used in combination. In this embodiment, the glass transition temperature of the monomer M3 as a homopolymer is preferably 70° C. or less. Furthermore, it is preferable that the degree of swelling in an electrolyte of the monomer M3 is 1.3 times or more, or the degree of swelling in an electrolyte cannot be measured due to dissolution in the electrolyte.
[0020] (Content of unit U1, unit U2 and unit U3) When the total units derived from the ethylenically unsaturated monomers constituting the first polymer particle are taken as 100% by mass, the content of the unit U1 is more than 50% by mass, and the content of the unit U2 is 5% or more and less than 50% by mass. In this way, since the unit U1 contributing as a softening component is the main component while a certain amount of the unit U2 is contained, the first polymer particle can achieve low electrolyte swelling, high strength and flexibility at the same time. From the same viewpoint as above, the content of the unit U1 is preferably 60% by mass or more, more preferably 65% by mass or more, and even more preferably 68% by mass or more. The upper limit of the content of the unit U1 is preferably 92.5% by mass or less, more preferably 90% by mass or less. Similarly, the content of the unit U2 is preferably 7.5% by mass or more and 40% by mass or less, more preferably 10% by mass or more and 35% by mass or less, and even more preferably 10% by mass or more and 32% by mass or less. In addition, from the viewpoints of low electrolyte swelling, high strength and flexibility, the total amount of units U1 and U2 is preferably 75.0% by mass or more and 100% by mass or less, and more preferably 85% by mass or more and 100% by mass or less, when all units derived from ethylenically unsaturated monomers constituting the first polymer particle are taken as 100% by mass. Furthermore, from the viewpoints of low electrolyte swelling, high strength and flexibility, the content of the optional unit U3 is preferably 0% by mass or more and 25.0% by mass or less, and more preferably 0% by mass or more and 15.0% by mass or less, when the total amount of units derived from the ethylenically unsaturated monomers constituting the first polymer particle is taken as 100% by mass. The content of each unit can be specified by analyzing the polymer particles by a conventional method, but can also be specified as the charge ratio of each monomer.
[0021] (Electrolyte swelling degree of polymer particles) The first polymer particles have a swelling degree in an electrolyte of 1.3 times or less. Here, the swelling degree in an electrolyte is an index for evaluating the resistance of the polymer particles to an electrolyte, and by having the swelling degree in an electrolyte of 1.3 times or less, the adhesion to the current collector and the separator can be maintained even in the electrolyte. From this viewpoint, the swelling degree in an electrolyte is preferably 1.25 times or less, and more preferably 1.2 times or less. The degree of swelling in an electrolyte can be measured by the method described in the examples below. In addition, the degree of swelling in an electrolyte solution can be adjusted to fall within the above range, for example, by including a preferred amount of the preferred monomer component described above as a constituent component of the polymer particles.
[0022] (Breaking strength of polymer particles S) The breaking strength S of the first polymer particles measured when swollen in an electrolyte solution is preferably 2 MPa or more. When the breaking strength S is 2 MPa or more, high strength tends to be ensured even when immersed in an electrolyte solution. From the same viewpoint as above, the breaking strength S is more preferably 5 MPa or more. The upper limit of the breaking strength S is not particularly limited, but may be, for example, 20 MPa or less. The breaking strength S can be measured by the method described in the examples below. Furthermore, the breaking strength S can be adjusted to fall within the above range, for example, by including a preferred amount of the preferred monomer component described above as a constituent component of the polymer particles.
[0023] (Elongation at break of polymer particles E) The breaking elongation E of the first polymer particles measured when swollen in an electrolyte solution is preferably 100% or more. By having a breaking elongation E of 100% or more, high flexibility tends to be ensured even when immersed in an electrolyte solution. From the same viewpoint as above, the breaking elongation E is more preferably 200% or more, and further preferably 300% or more. The upper limit of the breaking elongation E is not particularly limited, but may be, for example, 600% or less. The breaking elongation E can be measured by the method described in the examples below. Furthermore, the breaking elongation E can be adjusted to fall within the above range by, for example, including a preferred amount of the preferred monomer component described above as a constituent of the polymer particles.
[0024] In this embodiment, from the viewpoint of a balance between rebound characteristics and cycle characteristics, it is preferable that the breaking strength S of the first polymer particle is 2 MPa or more, and the breaking elongation E of the first polymer particle is 100% or more, both of which are measured when the first polymer particle is swollen in an electrolyte solution.
[0025] (Polymer particle breaking strength ratio R1) The breaking strength ratio R1 of the breaking strength S0 to the breaking strength S of the second polymer particles, obtained based on the following formula 1, is preferably ±40% or less. [Calculation of breaking strength ratio R1] Breaking strength ratio R1 = {(breaking strength S0 / breaking strength S)-1} x 100 (Equation 1) (In the above formula 1, the breaking strength S0 represents the breaking strength measured on the polymer particles before immersion in the electrolyte solution.) When the breaking strength ratio R1 is ±40% or less, the increase in the thickness of the secondary battery electrode before and after a certain number of charge / discharge cycles tends to be suppressed, and therefore the rebound characteristics tend to be improved. From the same viewpoint as above, the breaking strength ratio R1 is preferably ±35% or less, more preferably ±30% or less. The lower limit of the breaking strength ratio R1 is not particularly limited, but may be, for example, 0%. The breaking strength ratio R1 can be measured by the method described in the examples below. Furthermore, the breaking strength ratio R1 can be adjusted to fall within the above range by, for example, including a preferred amount of the preferred monomer component described above as a constituent component of the polymer particles.
[0026] (Polymer particle breaking strength ratio R2) The ratio R2 of the breaking elongation E0 to the breaking elongation E of the second polymer particles, obtained based on the following formula 2, is preferably ±10% or less. [Calculation of breaking elongation ratio R2] Breaking elongation ratio R2 = {(breaking elongation E0 / breaking elongation E) - 1} × 100 (Equation 2) (In the above formula 2, the breaking elongation E0 represents the breaking elongation measured on the polymer particles before immersion in the electrolyte solution.) When the breaking elongation ratio R2 is ±10% or less, the breakage of the conductive path in the secondary battery electrode before and after a certain charge / discharge cycle tends to be suppressed, and therefore the cycle characteristics tend to be improved. From the same viewpoint as above, the breaking strength ratio R2 is preferably ±9% or less, more preferably ±8% or less. The lower limit of the breaking strength ratio R2 is not particularly limited, but may be, for example, 0%. The breaking elongation ratio R2 can be measured by the method described in the examples described later. In addition, the breaking elongation ratio R2 can be adjusted to fall within the above range by, for example, containing a preferred amount of the above-mentioned preferred monomer component as a constituent of the polymer particles.
[0027] In this embodiment, from the viewpoint of the balance between the rebound characteristics and the cycle characteristics, it is preferable that the breaking strength ratio R1 between the breaking strength S0 of the first polymer particle and the breaking strength S, and the ratio R2 between the breaking elongation E0 of the polymer particle and the breaking elongation E, obtained based on the above formulas 1 and 2, are ±40% or less and ±10% or less, respectively.
[0028] (Second polymer particles) The second polymer particles are configured so that the electrolyte swelling degree, breaking strength S, and breaking elongation E fall within predetermined ranges.
[0029] (Electrolyte swelling degree of polymer particles) The second polymer particles have a swelling degree in an electrolyte of 1.3 times or less. Here, the swelling degree in an electrolyte is an index for evaluating the resistance of the polymer particles to an electrolyte, and by having the swelling degree in an electrolyte of 1.3 times or less, the adhesion to the current collector and the separator can be maintained even in the electrolyte. From this viewpoint, the swelling degree in an electrolyte is preferably 1.25 times or less, and more preferably 1.2 times or less. The degree of swelling in an electrolyte can be measured by the method described in the examples below. In addition, the electrolyte swelling degree can be adjusted to the above range, for example, by adopting a method for adjusting the electrolyte swelling degree, breaking strength S, breaking elongation E, breaking strength ratio R1, and breaking elongation ratio R2 (hereinafter, also simply referred to as the "adjustment method") described below.
[0030] (Breaking strength of polymer particles S) The breaking strength S of the second polymer particles measured when swollen in an electrolyte solution is 2 MPa or more. When the breaking strength S is 2 MPa or more, high strength is ensured even when immersed in an electrolyte solution. From the same viewpoint as above, the breaking strength S is preferably 5 MPa or more. The upper limit of the breaking strength S is not particularly limited, but may be, for example, 20 MPa or less. The breaking strength S can be measured by the method described in the examples below. Moreover, the breaking strength S can be adjusted to fall within the above range, for example, by employing the adjustment method described below.
[0031] (Elongation at break of polymer particles E) The breaking elongation E of the second polymer particles measured when swollen in an electrolyte solution is 100% or more. By having a breaking elongation E of 100% or more, high flexibility is ensured even when immersed in an electrolyte solution. From the same viewpoint as above, the breaking elongation E is preferably 200% or more, more preferably 300% or more. The upper limit of the breaking elongation E is not particularly limited, but may be, for example, 600% or less. The breaking elongation E can be measured by the method described in the examples below. Moreover, the breaking elongation E can be adjusted to fall within the above range, for example, by employing the adjustment method described below.
[0032] In this embodiment, from the viewpoint of a balance between rebound characteristics and cycle characteristics, the electrolyte swelling degree of the second polymer particles is 1.3 times or less, and the breaking strength S of the polymer particles measured when swollen in the electrolyte is 2 MPa or more, and the breaking elongation E of the polymer particles is 100% or more.
[0033] In this embodiment, from the viewpoint of the balance between the rebound characteristics and the cycle characteristics, it is preferable that the breaking strength ratio R1 between the breaking strength S0 of the polymer particle and the breaking strength S, and the ratio R2 between the breaking elongation E0 of the polymer particle and the breaking elongation E, obtained based on the above formulas 1 and 2, are ±40% or less and ±10% or less, respectively.
[0034] The second polymer particles may also have the above-mentioned units U1, U2, and U3. In addition, the contents of the units U1, U2, and U3 in the second polymer particles also preferably satisfy the above-mentioned numerical ranges.
[0035] It is particularly preferable that the polymer particles in this embodiment have the electrolyte swelling degree, breaking strength S, breaking elongation E, breaking strength ratio R1, and breaking elongation ratio R2, all of which are measured as described above, within the respective numerical ranges described above.
[0036] (Method of adjusting electrolyte swelling degree, breaking strength S, breaking elongation E, breaking strength ratio R1, and breaking elongation ratio R2) The present inventors have focused on the polarity difference (SP value difference) between the polymer composition for non-aqueous secondary batteries and the electrolyte, and have found that by selecting a material with low polarity, sufficient tensile strength and tensile elongation can be obtained even after immersion in the electrolyte. According to this finding, the method for adjusting the electrolyte swelling degree, breaking strength S, breaking elongation E, breaking strength ratio R1, and breaking elongation ratio R2 of the polymer particles in this embodiment to the above-mentioned numerical ranges is not limited to the above-mentioned method. That is, by focusing on the solubility parameter (hereinafter also referred to as "SP value") of the monomer component, and using the SP value of a general electrolyte as a standard, a monomer component with a high SP value and a monomer component with a low SP value can be used in combination, and by increasing or decreasing the content ratio while taking the SP value of each monomer component into consideration, the electrolyte swelling degree, breaking strength S, breaking elongation E, breaking strength ratio R1, and breaking elongation ratio R2 of the polymer particles in this embodiment can be adjusted to the above-mentioned numerical ranges. In this specification, the SP value means a solubility parameter δ calculated by the following formula (A) using the cohesive energy density (E) and molar volume (V) of various atomic groups described in "RF Edors: Polym. Eng. Sci., 14[2], 147-154(1974)". δ=ΣE / ΣV (A) (In formula (A), E and V respectively represent the E of various atomic groups and the molar volume V according to Fedors.)
[0037] The SP value of a typical electrolyte solution is, for example, about 11, but is not limited to the following. According to this example, a monomer component having an SP value of more than 11 can be treated as a high SP value component, and a monomer component having an SP value of less than 11 can be treated as a low SP value component. The ethylenic monomer M1 usually tends to have a low SP value. The SP value of the homopolymer constituted by the ethylenic monomer M1 is preferably, but not limited to, 8.0 to 9.5. Furthermore, the ethylenic monomer M2 generally tends to have a high SP value. The SP value of the ethylenic monomer M2 is preferably 12 to 17, although it is not limited thereto. In other words, when a low SP value component having an SP value of 8.0 to 9.5 and a high SP value component having an SP value of 12 to 17 are used in combination, it is preferable that the content of the former is more than 50 mass% and the content of the latter is 5% or more and less than 50 mass%.
[0038] (glass transition temperature) In order to further enhance flexibility, the polymer particles in this embodiment preferably have a maximum glass transition temperature of 20° C. or less, more preferably 10° C. or less, and even more preferably 0° C. or less, as measured by DSC. The above-mentioned glass transition temperatures can be measured by the method described in the Examples below, and can be adjusted to be within the above-mentioned ranges by, for example, containing preferred amounts of preferred monomer components described below as constituent components of the polymer particles.
[0039] (Average particle size) In order to further contribute to stress relaxation, the polymer particles in this embodiment preferably have an average particle size of 50 nm or more and 800 nm or less, more preferably 100 nm or more and 650 nm or less, and even more preferably 150 nm or more and 500 nm or less. The average particle size can be measured by the method described in the Examples below, and can be adjusted to the above range by adjusting the monomer composition ratio of the components constituting the polymer particles, the polymerization temperature, the emulsifier, etc.
[0040] (Application) The composition of the present embodiment may contain various known optional components in addition to the polymer particles of the present embodiment depending on the application. The application of the composition of the present embodiment is not particularly limited as long as it is used as one material of a non-aqueous secondary battery, and it can be used as a negative electrode material, a positive electrode material, a separator material, etc., but it is particularly preferable to use it as a negative electrode material. That is, the negative electrode for a non-aqueous secondary battery of the present embodiment (hereinafter, also simply referred to as "negative electrode") preferably contains the composition of the present embodiment.
[0041] Hereinafter, when the composition of the present embodiment is used for producing a negative electrode, a positive electrode, or a separator, it will be referred to as a "battery material production composition". Herein, when a negative electrode is produced using the battery material production composition, the battery material production composition may contain the polymer particles of the present embodiment, a negative electrode active material, and optional components as required. When a positive electrode is produced using the battery material production composition, the battery material production composition may contain the polymer particles of the present embodiment, a positive electrode active material, and optional components as required. Furthermore, when a separator is produced using the battery material production composition, the battery material production composition may contain the polymer particles of the present embodiment, a separator raw material, and optional components as required. On the other hand, when the composition of the present embodiment does not contain any of the negative electrode active material, the positive electrode active material, and the separator raw material, it can be used as an additive for manufacturing battery materials. That is, when the composition of the present embodiment is used as a binder, it is called a "binder composition", and when it is used as a thickener, it is called a "thickener composition". As described above, the term "composition of the present embodiment" can be said to include "composition for manufacturing a battery material," "composition for binder," and "composition for thickener," and all of the applications have in common the fact that the polymer particles of the present embodiment are contained. In addition, in all applications, when the composition of the present embodiment contains an optional component, the type, blending ratio, etc. of the optional component are not particularly limited, and may be appropriately determined depending on the application.
[0042] When a negative electrode is produced from the composition for producing a battery material, the negative electrode active material that can be used is not particularly limited, but examples thereof include carbon-based active materials and silicon-based active materials. The carbon-based active material is not particularly limited, but examples thereof include graphite, carbon fiber, coke, hard carbon, mesocarbon microbeads (MCMB), baked furfuryl alcohol resin (PFA), conductive polymers (poly-p-phenylene, etc.), and the like. The silicon-based active material is not particularly limited, but examples thereof include silicon, SiO x (0.01≦x<2), alloys of silicon and transition metals, etc.
[0043] When a positive electrode is manufactured using the composition for manufacturing a battery material, the positive electrode active material that can be used is not particularly limited, but examples thereof include lithium-containing composite oxides, transition metal oxides, transition metal fluorides, and transition metal sulfides. The lithium-containing composite oxide is not particularly limited, but examples thereof include LiCoO2, LiMnO2, LiNiO2, LiMn2O4, LiXCoYSnZO2, LiFePO4, and LiXCoYSnZO2. The transition metal oxide is not particularly limited, but examples thereof include MnO2, MoO3, V2O5, and V6O 13, Fe2O3, Fe3O4, etc. The transition metal fluoride is not particularly limited, but examples thereof include CuF2, NiF2, and the like. The transition metal sulfide is not particularly limited, but examples thereof include TiS2, TiS3, MoS3, and FeS2.
[0044] In this embodiment, the binder composition preferably contains the polymer particles of this embodiment and 0.0001 to 1.0 parts by mass of an isothiazolin-based compound relative to 100 parts by mass of the polymer particles. When the above range is satisfied, hysteretic viscosity behavior against shear force can be suppressed, and more stable coating properties tend to be exhibited. The isothiazolin-based compound is not particularly limited, and various known compounds can be used, such as 2-methyl-4-isothiazolin-3-one, 5-chloro-2-methyl-4-isothiazolin-3-one, 1,2-benzoisothiazolin-3-one, 2-n-octyl - 4-isothiazolin-3-one, 4,5-dichloro-2-n-octyl-4-isothiazolin-3-one, 2-ethyl-4-isothiazolin-3-one, 4,5-dichloro-2-cyclohexyl-4-isothiazolin-3-one, 5-chloro-2-ethyl-4-isothiazolin-3-one, 5-chloro-2-t-octyl-4-isothiazolin-3-one, 4-chloro-2-n-octyl-4-isothiazolin-3-one, 5-chloro-2-n-octyl-4-isothiazolin-3-one, Nn-butyl-1,2-benzisothiazolin-3-one benzoisothiazolin-3-one, N-butylbenzoisothiazolin-3-one, N-methylbenzoisothiazolin-3-one, N-ethylbenzoisothiazolin-3-one, N-propylbenzoisothiazolin-3-one, N-isobutylbenzoisothiazolin-3-one, N-pentylbenzoisothiazolin-3-one, N-isopentylbenzoisothiazolin-3-one, N-hexylbenzoisothiazolin-3-one, N-allylbenzoisothiazolin-3-one, N-(2-butenyl)benzoisothiazolin-3-one, etc. Among these, 2-methyl-4-isothiazolin-3-one is preferred. In addition, the binder composition of the present embodiment may contain a defoamer as an optional component. Examples of the defoaming agent include various defoaming agents based on mineral oil, silicone, acrylic, and polyether. When a defoaming agent is contained, the defoaming property tends to be more excellent. In this case, the types and blending ratios of the optional components are not particularly limited.
[0045] (Method of producing polymer composition for non-aqueous secondary battery) The method for producing the composition of the present embodiment is not particularly limited, but it can be preferably produced by the following production method (hereinafter also referred to as the "production method of the present embodiment"). That is, in order to obtain a composition containing polymer particles, a method of performing emulsion polymerization using the above-mentioned raw material monomers, etc. is preferred. Appropriate seed particles can be used during polymerization, and the seed particles can also be obtained by normal emulsion polymerization. In addition, a known method can be adopted for emulsion polymerization, and the composition can be produced by appropriately using a polymerization initiator, a molecular weight regulator, a chelating agent, a pH regulator, an emulsifier, etc. in an aqueous medium.
[0046] The emulsifier is not particularly limited, but for example, anionic surfactants, nonionic surfactants, amphoteric surfactants, reactive surfactants, etc. can be used alone or in combination of two or more kinds.
[0047] The anionic surfactant is not particularly limited, but examples thereof include sulfate esters of higher alcohols, alkylbenzene sulfonates, aliphatic sulfonates, and sulfate esters of polyethylene glycol alkyl ethers.
[0048] The nonionic surfactant is not particularly limited, but for example, alkyl ester type, alkyl ether type, alkyl phenyl ether type of polyethylene glycol, etc. may be used.
[0049] The amphoteric surfactant is not particularly limited, but examples thereof include betaines such as lauryl betaine and stearyl betaine, and amino acid surfactants such as lauryl-β-alanine, stearyl-β-alanine, and lauryl di(aminoethyl)glycine.
[0050] The reactive surfactant is not particularly limited, but examples thereof include polyoxyethylene alkylpropenylphenyl ether, α-[1-[(allyloxy)methyl]-2-(nonylphenoxy)ethyl]-ω-hydroxypolyoxyethylene, and the like.
[0051] The polymerization initiator is not particularly limited, and examples thereof include water-soluble polymerization initiators such as sodium persulfate, potassium persulfate, and ammonium persulfate, oil-soluble polymerization initiators such as benzoyl peroxide and lauryl peroxide, and redox-based polymerization initiators in combination with a reducing agent, which can be used alone or in combination.
[0052] In the production method of this embodiment, the conditions such as stirring speed, polymerization temperature, reaction (polymerization) time, etc. are not particularly limited as long as the composition of this embodiment can be obtained. Typically, the stirring speed can be usually 50 rpm or more and 500 rpm or less, the polymerization temperature can be usually 50 ° C. or more and 100 ° C. or less, and the reaction time can be usually 3 hours or more and 72 hours or less.
[0053] In the method of the present embodiment, after the polymer particles are obtained as described above, the polymer particles are dispersed in a dispersion medium as necessary, and an optional component is added to obtain the composition of the present embodiment. Water can be used as the dispersion medium, and an organic solvent suitable for the active material can also be used as necessary.
[0054] (Non-aqueous secondary battery) The nonaqueous secondary battery of the present embodiment can be manufactured using the composition of the present embodiment. In other words, the nonaqueous secondary battery of the present embodiment contains the composition of the present embodiment. When the nonaqueous secondary battery of the present embodiment is a lithium ion secondary battery, its typical components include a negative electrode, a negative electrode current collector, a positive electrode, a positive electrode current collector, a separator, and an electrolyte, and the nonaqueous secondary battery of the present embodiment may have at least one of its main components (negative electrode, positive electrode, and separator) obtained using the composition of the present embodiment, that is, at least one of its main components may contain the composition of the present embodiment. In the nonaqueous secondary battery of the present embodiment, it is preferable that the negative electrode contains the composition of the present embodiment among the above main components. Whether each component contains the composition of this embodiment can be specified based on whether or not the component contains the polymer particles of this embodiment.
[0055] The method for producing the non-aqueous secondary battery of this embodiment is not particularly limited. For example, in the case of a lithium ion secondary battery, the composition of this embodiment is applied to a current collector, heated, and dried to form a corresponding electrode, and the positive and negative electrodes are opposed to each other via a separator, and an electrolyte is injected and sealed. The negative electrode current collector is not particularly limited, but for example, copper foil is used, and the positive electrode current collector is not particularly limited, but for example, aluminum foil is used. The electrolyte is not particularly limited, but for example, an electrolyte such as LiClO4, LiBF4, or LiPF6 dissolved in an organic solvent can be used. The organic solvent is not particularly limited, but for example, ethers, ketones, lactones, nitriles, amines, amides, carbonates, chlorinated hydrocarbons, etc. can be mentioned, and representative examples include tetrahydrofuran, acetonitrile, butyronitrile, propylene carbonate, ethylene carbonate, and diethyl carbonate, and is used as one type or a mixture of two or more types.
[0056] The coating method is not particularly limited, and any coater head such as a reverse roll coater, a comma bar coater, a gravure coater, or an air knife coater can be used. The drying method is also not particularly limited, and examples thereof include drying by leaving the coating to dry, drying by blowing air, drying by hot air, drying by an infrared heater, and drying by a far infrared ray heater. CanadaThe drying temperature is not particularly limited, but the drying can be performed at 60°C to 150°C, for example. EXAMPLES
[0057] The present embodiment will be described in more detail below with reference to examples, but the present embodiment is not limited to these examples. For convenience of explanation, the following examples use terms such as "composition" and "coating liquid", but both of these terms are concepts that are included in the composition of the present embodiment.
[0058] [Example 1] 0.3 parts by mass of polyoxyethylene polycyclic phenyl ether sulfate ammonium salt (Newcoll 707SF) and 400 parts by mass of ion-exchanged water were added to a reactor, and the temperature was raised to 70°C while stirring and maintained. 0.5 parts by mass of sodium persulfate (hereinafter also referred to as "NPS") was added to this. A monomer solution containing 175 parts by mass of 2-ethylhexyl acrylate (hereinafter also referred to as "2-EHA"), 10 parts by mass of methacrylic acid (hereinafter also referred to as "MAA"), and 15 parts by mass of 1,9-nonanediol dimethacrylate (hereinafter also referred to as "1,9-ND") was added to this, along with 1.5 parts by mass of Newcoll 707SF and 400 parts by mass of ion-exchanged water. The resulting mixture was emulsified with a homogenizer, and the resulting emulsion was added dropwise. The temperature was kept at 70°C, and the addition was completed in 2.5 hours, after which polymerization was continued for 2 hours. Thereafter, the temperature was raised from 70° C. to 85° C. and maintained for 1.5 hours to complete the polymerization. The amounts of the monomer components were 87.5 parts by mass of 2-EHA, 5 parts by mass of MAA, and 7.5 parts by mass of 1,9-ND relative to 100 parts by mass of the total amount of the monomer components (units derived from all ethylenically unsaturated monomers: 2-EHA, MAA, and 1,9-ND). 0.0005 parts by mass of methylisothiazoline was added as an additive to 100 parts by mass of the obtained polymer particles, and then the mixture was filtered using a 200 μm mesh. The polymerization rate was 99%. The obtained polymer particles were neutralized by adding an aqueous solution of 13.8 parts by mass of sodium hydroxide in 83.8 parts by mass of ion-exchanged water to obtain a composition. The obtained composition had a pH of 7 and a solid content of 18%. The polymerization rate was calculated by adding the solid content rate to the ratio of the amount of the residue to the amount of all the charged components. Using this composition, a secondary battery negative electrode was produced as follows.
[0059] <Preparation of coating solution for secondary battery negative electrode> To 1.5 parts by mass of the obtained composition, 1.0 parts by mass of carboxymethyl cellulose as a thickener component and 100 parts by mass of natural graphite as a negative electrode active material were further added, and ion-exchanged water was added thereto and stirred with a mechanical stirrer to prepare a total solid content of 60%. This was used as a premix, and then dispersed for 30 seconds at a peripheral speed of 20 m / s using a thin film rotating high-speed mixer (TK Filmmix FM56-L type (product name) manufactured by PRIMIX Co., Ltd.) to prepare a coating liquid for secondary battery negative electrodes.
[0060] <Preparation of secondary battery negative electrode> The coating solution was applied to one side of a copper foil using a die coater so that the thickness after drying was 100 μm, and then dried at 60° C. for 60 minutes. After drying at 120° C. for 3 minutes, the foil was compression molded using a roll press. The amount of the negative electrode active material applied was 106 g / m 2 , the bulk density of the negative electrode active material is 1.35 g / cm 3 It was made to be like this.
[0061] The composition and the secondary battery negative electrode obtained as described above were used to evaluate various physical properties as described below. The results are shown in Table 1.
[0062] [Examples 2 to 5 and Comparative Examples 1 to 4] In each example, the compositions of Examples 2 to 5 and Comparative Examples 1 to 4 were prepared and secondary battery negative electrodes were produced in the same manner as in Example 1, except that the types and / or amounts of monomers and additives were changed as shown in Table 1. The composition and the secondary battery negative electrode obtained as described above were used to evaluate various physical properties as described below. The results are shown in Table 1.
[0063] [Example 6] 0.3 parts by mass of Newcoal 707SF, 400 parts by mass of ion-exchanged water, and 10 parts by mass of MAA were added to the reactor, and the temperature was raised to 70°C while stirring and maintained. 0.5 parts by mass of NPS was added thereto. A monomer solution containing 159.8 parts by mass of 2-EHA, 30 parts by mass of MAA, and 0.2 parts by mass of 1,9-ND, 1.5 parts by mass of Newcoal 707SF, and 400 parts by mass of ion-exchanged water were added thereto. The resulting mixture was emulsified with a homogenizer, and the resulting emulsion was added dropwise. The temperature was kept at 70°C, and the dropwise addition was completed in 2.5 hours, after which polymerization was continued for 2 hours. The temperature was then raised from 70°C to 85°C, and maintained for 1.5 hours to complete the polymerization. The amount of each monomer component was 79.9 parts by mass of 2-EHA, 20 parts by mass of MAA, and 0.1 parts by mass of 1,9-ND relative to 100 parts by mass of the total amount of the monomer components (units derived from all ethylenically unsaturated monomers: 2-EHA, MAA, and 1,9-ND). Thereafter, in the same manner as in Example 1, a composition was prepared and a secondary battery negative electrode was produced. The composition and the secondary battery negative electrode obtained as described above were used to evaluate various physical properties as described below. The results are shown in Table 1.
[0064] (Average particle size) The average particle size of the polymer particles was measured using a particle size measuring device (Microtrac UPA150, manufactured by Nikkiso Co., Ltd.) The measurement conditions were a loading index of 0.15 to 0.3, and a measurement time of 300 seconds, and the numerical value of the 50% particle size in the obtained data was taken as the average particle size by dynamic light scattering.
[0065] (Electrolyte swelling degree) The composition containing the polymer particles was left to stand in an oven at 130°C for 1 hour and dried. The film of the polymer particles obtained by drying was cut to 0.5g. The cut sample was placed in a 50mL vial together with 10g of a mixed solvent of ethylene carbonate / ethyl methyl carbonate = 1 / 2 (volume ratio), and the mixed solvent was allowed to penetrate at 60°C for 1 day, after which the sample was taken out, washed with the mixed solvent, and the mass (Wa:g) was measured. The sample was then left to stand in an oven at 150°C for 1 hour, after which the mass was measured (Wb:g), and the swelling degree of the copolymer with respect to the electrolyte was calculated according to the following formula. Swelling degree of polymer particles in electrolyte (times) = 1 + {(Wa-Wb) / (Wb)} Regarding the electrolyte swelling degree of the homopolymer obtained by polymerizing each monomer, a sample (0.5 g of the polymer particle film obtained by drying) was taken from the homopolymer obtained as follows, and the electrolyte swelling degree was calculated based on the method described above. A homopolymer was prepared by the following method using each of the monomers used in Examples 1 to 6 and Comparative Examples 1 to 5, and a film was formed using the homopolymer in the same manner as above, and evaluated. Monomers whose homopolymers were insoluble in water (2-EHA, 1,9-ND, EA, BA, GMA, St, and BD) were prepared by emulsion polymerization in water as follows. 0.3 parts by mass of polyoxyethylene polycyclic phenyl ether sulfate ammonium salt (New Coal 707SF) and 400 parts by mass of ion-exchanged water were added to a reactor, and the temperature was raised to 70°C while stirring and maintained. 0.5 parts by mass of sodium persulfate (hereinafter also referred to as "NPS") was added thereto. 100 parts by mass of the above monomer, 1.5 parts by mass of New Coal 707SF, and 500 parts by mass of ion-exchanged water were added thereto. The resulting mixture was emulsified with a homogenizer, and the resulting emulsion was added dropwise. The temperature was kept at 70°C, and the dropwise addition was completed in 2.5 hours, after which polymerization was continued for 2 hours. The temperature was then raised from 70°C to 85°C, and maintained for 1.5 hours to complete the polymerization, and the corresponding homopolymer was obtained. Moreover, a monomer (MAA) whose homopolymer was soluble in water was prepared by solution polymerization in water as follows. 100 parts by weight of methacrylic acid and 900 parts by weight of ion-exchanged water were added to a reactor, and the temperature was raised to 70° C. while stirring and maintained at that temperature. 0.5 parts by weight of sodium persulfate (hereinafter also referred to as “NPS”) was added thereto. Polymerization was continued for 4.5 hours while maintaining the temperature at 70° C. Thereafter, the temperature was raised from 70° C. to 85° C. and maintained for 1.5 hours to complete the polymerization, and the corresponding homopolymer was obtained.
[0066] (glass transition temperature) The composition containing the polymer particles was adjusted to pH 7.0 and dried at 130°C for 30 minutes to obtain a dried product. Using a differential scanning calorimeter (manufactured by SII Nano Technology Co., Ltd.; DSC6220), the temperature was raised from -50°C to +200°C at a rate of 20°C / min according to the ASTM method (D3418-97), a differential scanning calorimeter curve of the polymer particles was obtained, and the glass transition temperature was determined using the attached software. Whether the glass transition temperature was one or two or more was determined by finding the peaks by judging by the software. The glass transition temperature of each monomer was measured in the same manner as above, except that the corresponding homopolymer obtained by the method described in the above section (degree of swelling in electrolyte solution) was used.
[0067] (SP value) The SP value of the monomer used was determined by calculating the solubility parameter δ using the cohesive energy density (E) and molar volume (V) of various atomic groups described in "RF Edors: Polym. Eng. Sci., 14 [2], 147-154 (1974)" according to the following formula (A): δ=ΣE / ΣV (A) (In formula (A), E and V respectively represent the E of various atomic groups and the molar volume V according to Fedors.)
[0068] (Breaking strength and breaking elongation) A mold of 100 mm wide x 100 mm long x 20 mm high was placed on a smooth aluminum plate. 11 g of a composition (aqueous dispersion) containing polymer particles adjusted to a solid content of 18% was poured into the mold. This was dried at room temperature for 24 hours, and then dried at 100°C for 1 hour to obtain a film with a thickness of 200 μm. The obtained film was cut to produce a film with a length of 1 cm x width of 8 cm. The produced film was stretched at a speed of 50 mm / min in accordance with JIS-K5301, and the strength at break was measured three times. The average value of the strength and the average value of the elongation at break were designated as the breaking strength S and the breaking elongation E, respectively. Next, the prepared film was cut out separately, and the test piece was immersed in a mixed solvent of ethylene carbonate / ethyl methyl carbonate = 1 / 2 (volume ratio) at 60 ° C. for one week. After that, the test piece was dried at 60 ° C. for one day, and the breaking strength S0 and breaking strength S1 were measured in the same manner as above. Elongation E0 was measured. Furthermore, the breaking strength ratio R1 and the breaking elongation ratio R2 were calculated based on the following formulas 1 and 2. Breaking strength ratio R1 = {(breaking strength S0 / breaking strength S)-1} x 100 (Equation 1) Breaking strength ratio R2 = {(breaking elongation E0 / breaking elongation E) - 1} x 100 (Equation 2)
[0069] (Peel strength) A test piece measuring 2 cm wide x 12 cm long was cut out from the obtained negative electrode of the secondary battery, and the surface of the current collector side of the test piece was attached to an aluminum plate with double-sided tape. In accordance with JIS Z 1522, a tape measuring 18 mm wide (trade name "Cellotape (registered trademark)" (manufactured by Nichiban Co., Ltd.)) was attached to the electrode layer side of the test piece, and the strength when the tape was peeled off in a 180° direction at a speed of 100 mm / min was measured six times, and the average value (N / 18 mm) was calculated as the peel strength (before immersion in electrolyte). Next, a test piece measuring 2 cm wide x 12 cm long was separately cut out from the negative electrode of the secondary battery, and this test piece was immersed in a mixed solvent of ethylene carbonate / ethyl methyl carbonate = 1 / 2 (volume ratio) at 80 ° C. for one week. After that, the test piece was dried at 80 ° C. for one day, and the peel strength (after immersion in electrolyte) was measured in the same manner as above. The larger these values are, the higher the adhesive strength between the current collector and the electrode layer is, and the more difficult it is to peel the electrode layer from the current collector. Specifically, the peel strength was evaluated based on the following criteria. ◎:40N / m or more ○: 30N / m or more and less than 40N / m △: 20N / m or more and less than 30N / m ×: Less than 20N / m
[0070] (Springback) The negative electrode of a secondary battery immediately after being obtained by the method described in the section (Preparation of a negative electrode of a secondary battery) (bulk density of the negative electrode active material: 1.35 g / cm 3 The difference between the thickness at the initial stage and the thickness after leaving it for one day was taken as springback and was evaluated based on the following criteria. ◎: Less than 5μm ○: 5μm or more and less than 10μm △: 10μm or more and less than 15μm ×: 15μm or more
[0071] (Rebound) The obtained secondary battery negative electrode was pressed and left for one day, and from the thickness thereof, an electrolyte solution described below was injected, and the thickness of the electrode layer after 100 cycles of charge and discharge were measured. Rebound property = (thickness of electrode layer after 100 charge / discharge cycles) - (thickness after pressing and leaving for 1 day) The evaluation was based on the following criteria. ◎: Less than 10μm ○: 10μm or more and less than 15μm △: 15μm or more and less than 20μm ×: 20μm or more
[0072] (Initial capacity, temperature cycle test and cycle characteristics) A secondary battery manufactured by the following method using a secondary battery negative electrode was charged at a constant current of 2C at 60°C using a constant current / constant voltage charging method until the battery reached 4.2V, then charged at a constant voltage, and then discharged at a constant current of 2C until the battery reached 3.0V. A charge / discharge cycle was performed in which the initial discharge capacity was judged according to the following criteria. The larger this value, the smaller the capacity loss due to the initial charge / discharge. The cycle test was performed up to 100 cycles, and the ratio of the discharge capacity at the 100th cycle to the initial discharge capacity was taken as the capacity retention rate, and judged according to the following criteria. The larger this value, the smaller the capacity loss due to repeated charge / discharge. (Initial capacity) ◎: Initial discharge capacity is 12.0mAh or more 〇: Initial discharge capacity is 11.5mAh or more and less than 12.0mAh △: Initial discharge capacity is 11.0mAh or more and less than 11.5mAh ×: Initial discharge capacity is less than 11.0mAh (Cycle characteristics) ◎: Capacity retention rate is 90% or more 〇: Capacity retention rate is 80% or more but less than 90% △: Capacity retention rate is between 70% and 80% ×: Capacity retention rate is less than 70%
[0073] <Preparation of secondary battery> The positive and negative electrodes of the secondary battery were punched into a circle, and the positive electrode, separator, and negative electrode were laminated in this order so that the active material surfaces of the positive and negative electrodes faced each other, and then the laminate was placed in a stainless steel metal container with a lid. The container and the lid were insulated, and the container was placed so that it was in contact with the copper foil of the negative electrode, and the lid was placed so that it was in contact with the aluminum foil of the positive electrode. Then, the electrolyte was poured into the container, which was then sealed, and the container was left at room temperature for one day to prepare a secondary battery. The electrolyte used here was prepared by dissolving LiPF6 as a solute in a mixed solvent of ethylene carbonate / ethyl methyl carbonate = 1 / 2 (volume ratio) to a concentration of 1.0 mol / L. The separator used was made of a porous polyethylene film, and the secondary battery negative electrodes obtained in Examples 1 to 5 and Comparative Examples 1 to 4 were used as the secondary battery negative electrodes. Furthermore, the positive electrode of the secondary battery was prepared as follows. A slurry was prepared by dispersing 92.2 mass% of lithium cobalt composite oxide (LiCoO2) as the positive electrode active material, 2.3 mass% each of flake graphite and acetylene black as the conductive material, and 3.2 mass% of polyvinylidene fluoride (PVDF) as the binder in N-methylpyrrolidone (NMP). This slurry was applied to one side of a 20 μm thick aluminum foil that serves as a positive electrode current collector using a die coater, dried at 130 °C for 3 minutes, and then compression molded using a roll press machine. At this time, the amount of active material applied to the positive electrode was 250 g / m 2 , the bulk density of the active material is 3.00 g / cm 3 The electrode thus obtained was used as a positive electrode for a secondary battery.
[0074] [Table 1]
[0075] In Table 1, the following abbreviations are used: EA: Ethyl acrylate BA: n-butyl acrylate GMA: glycidyl methacrylate St: styrene BD: Butadiene
[0076] Regarding the parts by mass of each monomer component in Table 1, in Examples 2 to 4, the standard is 100 parts by mass as in Example 1, while in Example 5 and Comparative Example 2, the total amount of 2-EHA and MAA is 100 parts by mass, and in Comparative Example 1, the total amount of 2-EHA and 1,9-ND is 100 parts by mass. In Comparative Example 3, the total amount of 2-EHA, MAA, EA, and GMA is 100 parts by mass, and in Comparative Example 4, the total amount of BA, St, BD, and polyacrylic acid is 100 parts by mass.
[0077] The glass transition temperatures and electrolyte swelling values measured for the homopolymers of the monomers used are given in Table 2 below.
[0078] [Table 2]
[0079] This application is based on a Japanese patent application (Patent Application No. 2020-207375) filed on December 15, 2020, the contents of which are incorporated herein by reference.
Claims
1. A polymer composition for a non-aqueous secondary battery, comprising polymer particles having a unit U1 derived from an ethylenic monomer M1 and a unit U2 derived from an ethylenic monomer M2, the ethylenic monomer M1 has a glass transition temperature as a homopolymer of −60° C. or lower, and a degree of swelling in an electrolyte of the ethylenic monomer M1 of 1.4 times or lower; the ethylenic monomer M2 has a glass transition temperature as a homopolymer of 100° C. or higher, and has a degree of swelling in an electrolyte of 1.2 times or less; When all units derived from ethylenically unsaturated monomers constituting the polymer particles are taken as 100 mass%, the content of the unit U1 is more than 65 mass%, and the content of the unit U2 is 5 mass% or more and less than 35 mass%, The degree of swelling of the polymer particles in an electrolyte solution is 1.3 times or less, The polymer particles have an average particle size of 100 nm or more and 650 nm or less.
2. The polymer composition for a non-aqueous secondary battery as described in claim 1, wherein when all units derived from ethylenically unsaturated monomers constituting the polymer particles are 100 mass%, the total content of the units U1 and the content of the units U2 is 92.5 mass% or more.
3. 3. The polymer composition for a nonaqueous secondary battery according to claim 1, wherein the polymer particles have a breaking strength S of 2 MPa or more and a breaking elongation E of 100% or more, which are measured when the polymer particles are swollen with an electrolyte solution.
4. The breaking strength S of the polymer particles is obtained based on the following formulas 1 and 2. 0 The breaking strength ratio R1 between the breaking strength S and the breaking elongation E of the polymer particles 0 4. The polymer composition for a non-aqueous secondary battery according to claim 3, wherein a ratio R2 of the breaking elongation E to the breaking elongation E is ±40% or less and ±10% or less, respectively. [Calculation of breaking strength ratio R1] Breaking strength ratio R1 = {(breaking strength S 0 / breaking strength S) - 1} x 100 (Equation 1) (In the above formula 1, the breaking strength S 0 represents the breaking strength measured on the polymer particles before immersion in the electrolyte solution.) [Calculation of breaking elongation ratio R2] Breaking strength ratio R2 = {(breaking elongation E 0 / breaking elongation E) - 1} x 100 (Equation 2) (In the above formula 2, the breaking elongation E 0 represents the breaking elongation measured on the polymer particles before immersion in the electrolyte solution.)
5. The polymer composition for non-aqueous secondary batteries according to any one of claims 1 to 4, wherein the ethylenic monomer M1 comprises 2-ethylhexyl acrylate.
6. The polymer composition for non-aqueous secondary batteries according to any one of claims 1 to 5, wherein the ethylenic monomer M2 comprises an ethylenically unsaturated carboxylic acid or an alkali metal salt thereof.
7. The polymer composition for non-aqueous secondary batteries according to any one of claims 1 to 6, wherein the ethylenic monomer M2 comprises (meth)acrylic acid or an alkali metal salt thereof.
8. 8. The polymer composition for a non-aqueous secondary battery according to claim 1, wherein the maximum glass transition temperature of the polymer particles measured by DSC is 20° C. or lower.
9. The polymer composition for non-aqueous secondary batteries according to any one of claims 1 to 8, further comprising 0.0001 parts by mass or more and 1.0 parts by mass or less of an isothiazolinone compound relative to 100 parts by mass of the polymer particles.
10. A polymer composition for a non-aqueous secondary battery comprising polymer particles, The degree of swelling of the polymer particles in an electrolyte solution is 1.3 times or less, The average particle size of the polymer particles is 100 nm or more and 650 nm or less, The polymer composition for a non-aqueous secondary battery, wherein the polymer particles have a breaking strength S of 2 MPa or more and a breaking elongation E of 100% or more, which are measured when the polymer particles are swollen in an electrolyte solution.
11. The breaking strength S of the polymer particles is obtained based on the following formulas 1 and 2. 0 The breaking strength ratio R1 between the breaking strength S and the breaking elongation E of the polymer particles 0 The polymer composition for a non-aqueous secondary battery according to claim 10 , wherein a ratio R2 of the elongation at break E to the elongation at break E is ±40% or less and ±10% or less, respectively. [Calculation of breaking strength ratio R1] Breaking strength ratio R1 = {(breaking strength S 0 / breaking strength S) - 1} x 100 (Equation 1) (In the above formula 1, the breaking strength S 0 represents the breaking strength measured on the polymer particles before immersion in the electrolyte solution.) [Calculation of breaking elongation ratio R2] Breaking strength ratio R2 = {(breaking elongation E 0 / breaking elongation E) - 1} x 100 (Equation 2) (In the above formula 2, the breaking elongation E 0 represents the breaking elongation measured on the polymer particles before immersion in the electrolyte solution.)
12. A negative electrode for a non-aqueous secondary battery, comprising the polymer composition for a non-aqueous secondary battery according to any one of claims 1 to 11.
13. 12. Use of the polymer composition for a non-aqueous secondary battery according to claim 1 as a material for a negative electrode of a non-aqueous secondary battery.
14. A non-aqueous secondary battery comprising the polymer composition for non-aqueous secondary batteries according to any one of claims 1 to 11.
Citation Information
Patent Citations
Production of white modified phenolic resin composition
JP1985090213A
Nonaqueous secondary battery
JP1996287915A
Binder composition for lithium ion secondary battery and its use
JP2000195521A
Aqueous electrode binder for secondary battery
JP2014130702A
Binder of lithium ion secondary battery electrode, slurry for electrodes, lithium ion secondary battery electrode, and lithium ion secondary battery
JP2014175106A